PREVALENCE OF GROUP A BOVINE ROTA VIRUS IN NEONATAL CALVES IN PUNJAB, PAKISTAN - N. Mukhtar1; T. Yaqub; M. Munir; J. Nazir; A. Aslam; A. Masood; Z. Tahir; M. Javed1and A. Nadeem (Journal of Animal and Plant Sciences, 2017)
Neonatal calf diarrhea is one of the main economic losses to dairy industry in developing countries.Study was planned to assess the prevalence of rotavirus diarrhea in Pakistan. Fecal samples (n=200) from cattle and buffalo diarrheic calves, age<3months were collected aseptically from ten districts of Punjab province selected on the basis of agro-ecological zones (canal fed, rain fed, desert and Pothohar).Commercially available ELISA kit was used for rotavirus detection. Results revealed 6% positivityincluding 3% from cattle calves and 4% from buffalo calves. District wise analysis showed higher prevalence(4%) in Lahore as compared to Faisalabad district(2%).Statistically significant (P<0.05) correlation was found between diarrhea and age groups of calf showing<1month susceptible for diarrhea, similarly significant association was found among gender, housing type, feeding pattern and season.We could not establish any correlation between species.Statistical analysis showed significant correlation between diarrhea incidences and source of water as canal water, underground and tap water. The present findings revealed rotavirus infection in calves in Pakistan that needs to be addressed using vaccine and improving livestock management.
Keywords: Neonatal diarrhea; Rotavirus; ELISA; Punjab; Pakistan